Studi Kajian Pembuatan Asam Oksalat Dengan Variasi Kecepatan Pengadukan Dan Lama Waktu Pengadukan Dari Bahan Dasar Ampas Tebu - Afriandi Afriandi; Fajril Akbar; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bagasse is a by product from the processing of sugar cane into sugar. The growing number of bagasse quantitatively into environmental problems that require attention and special handling. The purpose of this research was conducted to study the effect of stirring speed variation and stirring time. Bagasse was reduced in size to 40 mesh, then added 250 ml of 4 N NaOH solution and stirred at a speed of 300 rpm for 20 minutes, after which the samples were heated in an oven at a temperature of 180 0C for 75 minutes, then the samples are removed and added to hot water ± 150 ml, then filtered and washed until the filtrate is clear. Samples added CaCl2 10% solution of 250 ml until the precipitate formed is then filtered, then the precipitate was dissolved by H2SO4 2 M, then filtered and washed using 96% ethanol as much as 15 ml. The filtrate heated using a water bath at a temperature of 70 0C ± 1 hr, then the filtrate cooled to oxalic acid precipitation in the form of white crystals. Results obtained was purified by recrystallization process using ethanol 96%. The crystals that formed were analyzed qualitatively and quantitatively, the qualitative analysis carried out by the test Fourier Transform Infrared Spectroscopy (FTIR), while the quantitative analysis conducted by test melting point of the Melting Point Apparatus and calculate yield. Based on the research that has been done obtained yield (%) highest oxalic acid at stirring speed of 600 rpm and a stirring time of 50 minutes long as many as 0.92 grams, with a yield (%) of 6.133%.Keywords : Bagasse, calcium chloride, oxalic acid, sodium hydroxide, sulfate acid